A framework for assessing the impact of disease treatment. Issue 2 (1st February 2022) - Hassoun, Nicole; Friedman, Jacob; Cosler, Leon E.
Abstract: Objectives: To address ongoing pandemics and epidemics, policy makers need good data not only on the need for treatments but also on new interventions' impacts. We present a mathematical model of medicines' health consequences using disease surveillance data to inform health policy and scientific research that can be extended to address the current public health crisis. Methods: The Global Health Impact index calculates the amount of mortality and morbidity averted by key medicines for malaria, TB, HIV/AIDS and several Neglected Tropical Diseases (NTDs) using data on outcomes in the absence of treatment, treatment effectiveness and access to needed treatment. Country‐level data were extracted from data repositories maintained by the Global Burden of Disease study, Global Health Observatory, WHO, UNICEF and a review of the scientific literature. Results: The index aggregates drug impact by country, disease, company and treatment regimen to identify the spatial and temporal patterns of treatment impact and can be extended across multiple diseases. Approximately 62 million life‐years were saved by key drugs that target malaria, TB, HIV/AIDS and NTDs in our latest model year. Malaria and TB medicines together were responsible for alleviating 95% of this burden, while HIV/AIDS and NTD medicines contribute 4% and 1%, respectively. However, the burden of disease in the absence of treatment was nearly evenly distributed among malaria, TB and HIV/AIDS. Conclusions: A common framework that standardises health impact across diseases and their interventions can aid in identifying current shortcomings on a global scale.